African Zionism and its contribution to African Christianity in South Africa - Resane, K. Thomas (Scriptura, 2020)
The paper highlights the historical development of African Zionism, with special reference to the four major messianic churches. Socio-political conditions and other factors contributed to the formation of African Zionism. Israel’s nationalist theology of the temple and the John Alexander Dowie’s Zion City concepts played a significant role in influencing the formation of African Zionism. The churches selected for the study are Zion Christian Church, Shembe’s AmaNazaretha, International Pentecost Church, and St John’s Apostolic Faith Mission. The focus is on the spiritual significance of the cultic centre as perceived by these church formations. The reasons for pilgrimages to the centre are elaborated on, and the contribution of these churches to African Christianity are highlighted.